Review of International Practices for Determining Medium Term Resource Needs of Spending Agencies - Di Francesco, Michael (World Bank, Washington, DC, 2015)
This volume presents two research reports carried out with the objective of advancing practical knowledge in costing and use of cost information in the public sector. Both reports were carried out with support of the Governance Partnership Facility Trust Fund and in partnership between the Brazilian and Indonesian country offices of the World Bank. The first report aims to review international practices for determining medium term resource needs of spending agencies (what is also referred to as bottom-up costing for medium term expenditure frameworks). The principal objective is to compile comparative information on practices and methodologies used by selected OECD countries to determine program costs as part of their medium term expenditure planning. The second report details the experiences of three selected subnational governments in Brazil: Sao Paulo, Rio Grande do Sul and Pernambuco with the development and use of cost information. The main objective is to present comparative information on practices adopted by these jurisdictions. It is expected that this volume helps to fill a gap in the technical literature by presenting practical examples of the development and use of cost information within budgetary and fiscal planning frameworks in advanced and developing countries both at the national and subnational level.